PENGARUH HARGA, KUALITAS PRODUK DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA PELANGGAN MR. K CAFE CABANG JL. KI MANGUNSARKORO 15 SEMARANG) - Dyah Eka Pratiwi; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2018)
The company as an organization that has a goal to generate profits is inseparable from the role of marketing strategies in the company, including purchasing decisions. This research was conducted as a decline in sales at Mr. K Cafe in 2017, so we have to know what factors that influence the purchase decision. This study aims to determine consumer perceptions of price, product quality, location, and purchase decision of Mr. K Cafe, and then to determine the effect of price, product quality, and location against purchasing decision on Mr. K Cafe. The research data was collected from 100 Mr. K Cafe consumers who live in Semarang City. The type of research is explanatory research. The technique of sampling is non probability sampling based on purposive sampling method. The result of the research showed that the price influence the purchase decision at the amount 27,9%. Product quality influence the purchase decision at the amount 74,3%. Location influence the purchase decision at the amount 19,7%. Meanwhile, simultaneously price, product quality, and location influence the purchase decision at the amount 76,9% while the rest 23,1% influenced by the other factor beside price, product quality, and location. Based on the calculation of F Test shows that there is a positive influence between price, product quality, and location to purchasing decison. It is means the cheaper the price, the better the quality of product, and the more strategic the location, the higher purchasing decisions of food and drinks at Mr. K Cafe. In addition, product quality has the most dominant influence with regression coefficent value of 0,948. Suggestion in this research is to adjust the price of the product with the serving portion. In terms of product quality both taste and variety of products must be upgraded and improved. Moreover in terms of the location, it is need to improve access road to location.